AI Surveillance: The Panopticon Reimagined - Thit, Hninn Thanlwin (Politikon: The IAPSS Journal of Political Science, 2025)
This paper reinterprets Michel Foucault’s Panopticon in the context of AI-enabled surveillance, arguing that algorithmic monitoring now disciplines citizens through pervasive, opaque, and normalized forms of control. While such systems pose a direct threat to democratic freedoms, their global diffusion—evident from China’s practices in Xinjiang to predictive policing and spyware elsewhere—demands proactive and accountable governance. I contend that coordinated export controls, coupled with NGO-led exposure and strategic litigation, form an essential counter-disciplinary framework. Together, these mechanisms constrain abusive surveillance, strengthen democratic oversight, and enable citizens to resist becoming the docile bodies of an increasingly automated surveillance order.